Assessing Forms and Functions of Aggression in High School Students - Trang, Le Thi Huyen; Minh, Dang Hoang (VNU Journal of Science: Education Research; Vol 37 No 1, 2021)
This study aims to assess forms and functions of four simultaneous types of aggression in high school students. The cross-sectional study of 644 high school students was carried out in Hanoi and Hung Yen province. The Peer Conflict Scale, Youth Self-Report version,  was used. The results show that 99.4% of the students reporting aggressive behavior, with 30.4% reporting "often" and 20.8% reporting "always" performing at least one aggressive behavior. Also, according to the study results, reactive-overt aggression was the most reported, and proactive-overt aggression was the least reported. Unlike many previous studies’ results, the studied female students exhibited a higher level of aggression than the male students and the urban students were more aggressive than their rural peers. More importantly, positive correlation was found among the 4 types of agreesion. The study findings are expected to help develop effective classroom management plans and psychological support for students.